2022
DOI: 10.3390/en15051930
|View full text |Cite
|
Sign up to set email alerts
|

A Review about Flux-Weakening Operating Limits and Control Techniques for Synchronous Motor Drives

Abstract: This paper deals with motor design aspects and control strategies for the flux-weakening (FW) operation of synchronous motors. The theory of FW is described by taking into account different control schemes. The advantages and drawbacks of each one are discussed, as well. Moreover, some motor design considerations for achieving an effective FW operation are illustrated for permanent magnet (PM), wound rotor (WR) and reluctance (REL) synchronous machines, using the per unit approach. The distinguishing character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…FW algorithms modify the direct current of PM motors; however, this action may be carried out in several ways, and each approach has its own advantages and drawbacks. The authors of [32,33] analyze the existing methods and provide a brief review and classification. In their work, they divide the techniques into feedback, feedforward, and mixed methods.…”
Section: δωmentioning
confidence: 99%
“…FW algorithms modify the direct current of PM motors; however, this action may be carried out in several ways, and each approach has its own advantages and drawbacks. The authors of [32,33] analyze the existing methods and provide a brief review and classification. In their work, they divide the techniques into feedback, feedforward, and mixed methods.…”
Section: δωmentioning
confidence: 99%
“…The pull-down current reflects the driving capacity of the output circuit. During simulation, VBB is 30 V [8] . IN and CLK are clock signals with an amplitude of 5 V and a frequency of 10 KHz.…”
Section: Simulation Of Output Stage Circuitmentioning
confidence: 99%
“…In motor applications, this can be used to improve the performance of machines that are operated at a wide range of speeds. The benefits are related to field weakening [37,38], where the power and torque can be controlled depending on the operation speed. Such benefits have been studied by Cinti et al [34], who compared PM machines and HE machines, and showed the advantages of operating with a good efficiency at variable speeds.…”
Section: Advantage Of Variable Flux In Hybrid Excitationmentioning
confidence: 99%